The evaluation of two rotary instrumentation techniques under "operator-related variables" standardized conditions - Uzun, Ozgur; Topuz, Ozgur; Yalpi, Fatma; Unsal, Feyza; Aydin, Cumhur; Bodrumlu, Emre (European Journal of Dentistry, 2013)
Objective: We aimed here to evaluate the enlargement characteristics of two nickel-titanium rotary instrument systems that use two different preparation techniques, in simulated root canals under "operator-related variables" standardized conditions. Materials and Methods: A total of 40 simulated canals in resin blocks were divided into two groups as the Mtwo group for use with a single-length technique and the ProTaper instrument system group for use with crown down technique. To standardize the operator-related variables, all preparations were carried out with a computer controlled device that was developed and used previously as described in a published study. The pre- and post-operative digital images of the canals were superimposed and measured at 11 levels from the apical tip. The distances between the pre- and post-operative outer lines of the root canals were measured at both the inner and outer sides of the curve. The amount of removed material and the symmetry of the preparations were evaluated. Statistical analyses were performed with Mann-Whitney test. Results: Significantly more material was removed by Mtwo at 9 levels and by ProTaper at 2 levels (P < 0.05) while no significant difference was determined at 11 levels. The preparations made with ProTaper were more symmetrical at 4 levels while no significant difference was determined at 7 levels. Conclusions: Mtwo removed significantly more material than ProTaper at different levels of the curved root canals. Mtwo and ProTaper made symmetrical preparations and maintained the original shape of the root canal at different levels under controlled operator-related variables.
Keywords: Mtwo; preparation symmetry; ProTaper; resin blocks; rotary instrumentation